IMAGE (Integrated Methods for Advanced Geothermal Exploration) - Jousset, Philippe; Blanck, Hanna; Hersir, Gylfi P.; Kirk, Henning; Erbas, Kemal; Ágústsson, Kristján; Franke, Steven; Hensch, Martin; Bruhn, David; Huenges, Ernst (GFZ Data Services, 2020)
Abstract IMAGE is a two year seismological experiment realized at the Reykjanes Peninsula by Philippe Jousset (GFZ Potsdam) and Gylfi P. Hersir (ISOR Iceland). Reykjanes Peninsula is located at the southwestern tip of Iceland, at the emergent part of the Mid-oceanic Ridge. This area has a high seismicity and is exploited for its high geothermal potential. The deployment is performed to carry out a local seismological study with techniques such as seismic tomography (earthquake based, e.g. Jousset et al., 2016, and ambient noise e.g., Martins et al., 2020). The aim of the seismic experiment is to monitor the seismic activity associated with the rift processes (Blank et al., 2020) and/or the induced seismicity. The network comprised 30 onland stations (GIPP) and 21 Ocean Bottom Seismometers (Lobsters, DEPAS). Onland stations were deployed from April 2014 until August 2015 and comprise 20 broadband seismic stations (Nanometrics Trillium Compact 120 s), 10 short-period sensors (Mark sensors 1 Hz) and data loggers (DATA-CUBE) with acquisition frequencies of 200 Hz. Sensors were buried 30-40 cm deep in the ground in containers. Data gaps are minimal, and occurred every 3 months when the batteries were exchanged and data downloaded from the DATA-CUBEs. OBS were deployed in August 2014 and recorded for about a year. From this dataset, a catalogue of about 2000 earthquakes could be extracted. Waveform data are available from the GEOFON data centre, under network code 4L.